Sema6D Regulates Zebrafish Vascular Patterning and Motor Neuronal Axon Growth in Spinal Cord - Sheng, Jiajing; Xu, Jiehuan; Geng, Kaixi; Liu, Dong (Frontiers in Molecular Neuroscience, 2022)
Vessels and nerves are closely associated in anatomy as well as functions. Accumulating evidences have demonstrated that axon-guiding signals may affect endothelial cells migration and pathfinding, which is crucial for the patterning of both complex vascular network and neural system. However, studies regarding the functional overlap between vascular and neuronal orchestrating are still incomplete. Semaphorin6D (sema6D) belongs to the Semaphorin family and has been identified as an important regulating factor in diverse biological processes. Its roles in vascular development are still unclear. Here, we confirmed that sema6D is enriched in neural system and blood vessels of zebrafish embryos by in situ hybridization. Then, the deficiency of sema6D caused by specific antisense morpholino-oligonucleotides (MO) led to dramatic pathfinding defects in both intersegmental vessels (ISVs) and primary motor neurons (PMNs) of spinal cord in zebrafish embryos. Furthermore, these defective phenotypes were confirmed in F0 generation of sema6D knockouts and rescue experiments by overexpression of sema6D mRNA in sema6D morphants. These data collectively indicate that sema6D regulates zebrafish vascular patterning and motor neuronal axon growth in spinal cord, which might be of great therapeutical use to regulate vessel and nerve guidance in the relevant diseases that affect both systems.